PENYULUHAN TENTANG POLA KONSUMSI MENGGUNAKAN MEDIA POSTER ISI PIRING KU TERHADAP PENGETAHUAN, SIKAP DAN PERILAKU PADA IBU HAMIL DIWILAYAH KERJA PUSKESMAS KLUET SELATAN - Kiki Asrifa Dinen; Dian Rahayu; Ully Fitia; Meylissa SST MKM; Diana Lestari (Kreativitas Pada Pengabdian Masyarakat (Krepa), 2024)
The pregnancy period is part of the Window of Opportunity period. Throughout the pregnancy stage, pregnant women need to consume more food than before, the right food pattern, as well as a balanced intake of macronutrients. The nutritional status of pregnant women is determined by the consumption patterns of pregnant women before and during pregnancy. The percentage of energy and nutrient consumption of pregnant women in Indonesia in 2018 based on Nutrition (PSG), namely, energy consumption was only 73.6%, protein was 86.4%, carbohydrates were 76.8% and fat was 70%. Based on provinces in Indonesia, energy consumption among pregnant women is lowest, namely in the provinces of Maluku (48.5%), Lampung (58.6%), Papua (61%) and Aceh (64.1%). Consumption patterns can be influenced by several factors, including knowledge, attitudes and behavior of pregnant women. One effort to increase knowledge of pregnant women is education using poster media which can increase a person's knowledge. The aim of this research is to measure the effect of counseling about consumption patterns using poster media on the knowledge, attitudes and behavior of pregnant women in the South Kluet Health Center Work Area. This research is quantitative research with pre-experimental methods. The research design used was one group pretest-posttest design. This research was conducted in the South Kluet Health Center Working Area in 2024. The population in this study was all pregnant women in the South Kluet Health Center Working Area with a total of 42 people. The sampling technique in this research was Total Sampling, namely 42 people. From the results of the T test statistical research, there is an effect of counseling using poster media on knowledge, attitudes and behavior with p value results, knowledge has a sig-α of 0.000, attitude has a sig-α of 0.000 and attitude has a sig-α of 0.000, which means that there is a difference between knowledge, attitudes and behavior before and after being given counseling using poster media. The suggestion in this research is that it is hoped that it can be used as evaluation material in an effort to increase mothers' knowledge about healthy food consumption patterns and according to the needs of pregnant women so that their babies grow and develop healthily and the mother's nutrition is maintained at the South Kluet Health Center in the future